Об индефинитной интерполяционной задаче Шура - Неванлинны - Пика - Деркач, В.А. (Український математичний журнал, 2003)
Інтерполяційна задача Шура - Неванлінни - Піка, яка розглядається в класі узагальнених функцій Шура, зводиться до задачі розширення деякого ізометричного оператора V, що діє у просторі Понтрягіна. Опис розв'язків задачі базується на теорії М. Г. Крейна резольвентної матриці. The Schur–Nevanlinna–Pick interpolation problem is considered in the class of generalized Schur functions and reduced to the problem of the extension of a certain isometric operator V that acts in the Pontryagin space. The description of the solutions of this problem is based on the theory of the resolvent matrix developed by Krein.